2016
DOI: 10.15376/biores.11.3.6267-6285
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Saccharification of Acid/Alkali Pre-treated, Mill-run, and Depithed Sugarcane Bagasse

Abstract: aIn South Africa, approximately 3 × 10 6 tons of sugarcane bagasse is produced annually by 14 factories located on the north coast of KwaZuluNatal. It is one of the most readily available lignocellulosic materials for ethanol production through enzymatic saccharification and hydrolysis. Pre-treatment enables disruption of the naturally resistant structure of lignocellulosic biomass to make the cellulose accessible to hydrolysis for conversion to biofuels. In this study, pre-treatment of depithed bagasse and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Several microorganisms have been studied as alternative sources of cellulase for hydrolysis of cellulose; some of the reported organisms for this purpose include Candida tropicalis, Trichoderma harzianum, Aspergillus niger, Fusarium oxysporum, and Trichoderma sp. (Mattam et al, 2016;Mezule et al, 2016;Mkhize et al, 2016;Mishra and Jana, 2017). Recently, some authors (Hwangbo et al, 2019) reported a one-step saccharification of pretreated lignocellulosic biomass using immobilized magnetite biocatalyst system.…”
Section: Saccharification System For Converting Cellulose and Hemicel...mentioning
confidence: 99%
“…Several microorganisms have been studied as alternative sources of cellulase for hydrolysis of cellulose; some of the reported organisms for this purpose include Candida tropicalis, Trichoderma harzianum, Aspergillus niger, Fusarium oxysporum, and Trichoderma sp. (Mattam et al, 2016;Mezule et al, 2016;Mkhize et al, 2016;Mishra and Jana, 2017). Recently, some authors (Hwangbo et al, 2019) reported a one-step saccharification of pretreated lignocellulosic biomass using immobilized magnetite biocatalyst system.…”
Section: Saccharification System For Converting Cellulose and Hemicel...mentioning
confidence: 99%
“…The DSB was dried in an oven (Scientific, South Africa) at 105 °C for 24 h, milled using a Pulverisette 16 (Fritsch, Germany), and sieved to 40-mesh particle size. The procedure used for compositional analysis of DSB is explained in our previous study (Mkhize et al 2016).…”
Section: Compositional Analysis Of Dsbmentioning
confidence: 99%
“…When the pith is removed from SB, the resulting SB is called depithed sugarcane bagasse (DSB) (Mthembu et al 2020). When original bagasse (mill-run bagasse) was compared with the depithed sugarcane bagasse (Mkhize et al 2016), it was discovered that DSB is easier to handle, and it contains slightly more glucose. Hence, DSB was used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, a influência negativa da concentração inicial de glicose no rendimento do produto pode ser atribuída a uma combinação desses fatores complexos relacionados à bioquímica e à fisiologia microbiana. A porcentagem de biomassa solubilizada no pré-tratamento foi de 40% e as composições químicas do bagaço de cana-de-açúcar pré-tratado obtidas no presente estudo apresentaram-se similares aos valores reportados na literatura (Chen, Tu, Sheen, 2022;Mkhize, et al 2016;Rocha, et al 2011).…”
Section: Análise Estatísticaunclassified